2021
DOI: 10.3390/molecules26164756
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Catalysts for Formic Acid/Formate Electrooxidation

Abstract: Energy production and consumption without the use of fossil fuels are amongst the biggest challenges currently facing humankind and the scientific community. Huge efforts have been invested in creating technologies that enable closed carbon or carbon neutral fuel cycles, limiting CO2 emissions into the atmosphere. Formic acid/formate (FA) has attracted intense interest as a liquid fuel over the last half century, giving rise to a plethora of studies on catalysts for its efficient electrocatalytic oxidation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 161 publications
(395 reference statements)
0
7
0
Order By: Relevance
“…The viability of direct formic acid fuel cells (DFAFCs) intensely relies on efficient formic acid or formate electro-oxidation reactions (FAO or FORs). In general, Pt-or Pd-based materials are considered to be the most suitable and advanced catalysts for the efficiency of these reactions [2,6,7]. It is well known that FAO in acidic media occurs via two different reaction pathways on Pt [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The viability of direct formic acid fuel cells (DFAFCs) intensely relies on efficient formic acid or formate electro-oxidation reactions (FAO or FORs). In general, Pt-or Pd-based materials are considered to be the most suitable and advanced catalysts for the efficiency of these reactions [2,6,7]. It is well known that FAO in acidic media occurs via two different reaction pathways on Pt [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For the commercialization of DFAFCs, the performance of current electrocatalysts must be reinforced and the cost per unit of power should be reduced. [40,41] Several studies in the last few years have focused on finding inexpensive and efficient catalysts with enhanced catalytic activity and stability for FAO. Several review papers have been published recently to summarize the different aspects of electrocatalyst research for FAO.…”
Section: Electrocatalyst For Dfafcsmentioning
confidence: 99%
“…An ideal catalyst for FAO should show high activity, extended catalyst life, and low cost. For the commercialization of DFAFCs, the performance of current electrocatalysts must be reinforced and the cost per unit of power should be reduced [40,41] . Several studies in the last few years have focused on finding inexpensive and efficient catalysts with enhanced catalytic activity and stability for FAO.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, excessive exploitation of fossil fuels has caused both serious energy and environment crisis. Much attention has been now drawn on developing green and sustainable energy such as fuel cells. Direct formic acid fuel cells (DFAFCs) have been intensively investigated these days due to the advantages such as high power density, fast oxidation kinetics, environment friendly, wide range of renewable resources, etc. Pt-group metal nanomaterials have been the most widely used catalysts in DFAFCs due to their unique physical and chemical properties. However, the rare reserves and high cost of Pt-group metals seriously hinder the commercial application in large scale of this type fuel cells. , Research has already confirmed that the electrocatalytic performance of Pt-group metal nanocatalysts depended a lot on their structure such as size, morphology, surface structure, etc. Therefore, the rational design and preparation of Pt-group metal nanocatalysts with a specific morphology becomes a useful way to promote the electrocatalytic performance of Pt-group metal nanocatalysts.…”
Section: Introductionmentioning
confidence: 99%